Magnetic Electrodeposition of the Hierarchical Cobalt Oxide Nanostructure from Spent Lithium-Ion Batteries: Its Application as a Supercapacitor Electrode - Aboelazm, Eslam A. A.; Ali, Gomaa A. M.; Algarni, H.; Yin, Huajie; Zhong, Yu Lin; K. F., Chong (American Chemical Society, 2018)
In this study, electrodeposition of cobalt oxide (Co3O4) from spent lithium-ion batteries is successfully enhanced by the magnetic field effect. In the presence of magnetic field, well-defined hierarchical Co3O4 nanostructures with higher electroactive surface area are formed during the electrodeposition process. Electrochemical analysis shows that the enhanced Co3O4 nanostructures exhibit excellent charge storage capabilities of 1273 F g–1 at 1 A g–1, approximately 4 times higher than the electrodeposited Co3O4 that is formed without magnetic field effect. It also reveals the high cycling stability of enhanced Co3O4 nanostructures, with 96% capacitance retention at 5000 charge discharge cycles. The results manifest the enhancement of Co3O4 recovery from spent lithium-ion batteries, which can be the potential electrode material for supercapacitor application.